Efficacy and age-related effects of nitric oxide-releasing aspirin on experimental restenosis - Napoli, Claudio (The National Academy of Sciences, 2002)
Restenosis after percutaneous transluminal coronary angioplasty is caused by neointimal hyperplasia, which involves impairment of nitric oxide (NO)-dependent pathways, and may be further exacerbated by a concomitant aging process. We compared the effects of NO-releasing-aspirin (NCX-4016) and aspirin (ASA) on experimental restenosis in both adult and elderly rats. Moreover, to ascertain the efficacy of NCX-4016 during vascular aging, we fully characterized the release of bioactive NO by the drug. Sprague–Dawley rats aged 6 and 24 months were treated with NO releasing-aspirin (55 mg/kg) or ASA (30 mg/kg) for 7 days before and 21 days after standard carotid balloon injury. Histological examination and immunohistochemical double-staining were used to evaluate restenosis. Plasma nitrite and nitrate and S-nitrosothiols were determined by a chemiluminescence-based assay. Electron spin resonance was used for determining nitrosylhemoglobin. Treatment of aged rats with NCX-4016 was associated with increased bioactive NO, compared with ASA. NO aspirin, but not ASA, reduced experimental restenosis in old rats, an effect associated with reduced vascular smooth muscle cell proliferation. NCX-4016, but not ASA, was well tolerated and virtually devoid of gastric damage in either adult or old rats. Thus, impairment of NO-dependent mechanisms may be involved in the development of restenosis in old rats. We suggest that an NCX-4016 derivative could be an effective drug in reducing restenosis, especially in the presence of aging and/or gastrointestinal damage.